Contribuciones corológicas a la flora de los Montes de Toledo. - Navarro García, Patricia; Marcos Samaniego, Nieves (Botanica Complutensis, 1993)
MARCOs SAMANIEGO. N. & NAVARRO GAíwíA, P. 1993. Chorologic contributions to the Toledo Mounlains flora. Bat. Complutensis 18: 25 1-253 Seven <axa of chorological interesÉ for Toledo province are commented. We point op Rosa arven,s¡s Hudson and Festu<.a durancloi Clauson subsp. Mida (Hack) Rivas Ponce & Cebolla.